GAYA BAHASA PADA PUISI ANAK - Seha, Nur (ATAVISME, 2007)
Literature is a form of language performance and even in poetry genre. The element of that performance was quite conspicuous, such as the shape of rhyme and rhythm performance. Prerequirement for reading, hearing, and understanding of literature is mastery of the relevant language. It's effective for adults and child. Language is a purpose to understands the world that offered and purpose of increasing capability of children speech on listening, reading, speaking, and writing.